Ethical and effortful: workshopping human and generative AI academic writing collaborations - Johanna Amos (Journal of Learning Development in Higher Education)
The launch of Open AI’s ChatGPT in 2022 caused a furore within higher education. While initial reactions were negative – educators imagined the end of the undergraduate essay and an acceleration in academic integrity departures – more recent conversations have emphasised how these tools might enhance teaching and learning experiences. This paper explores one possibility for approaching student use of generative artificial intelligence (GenAI) tools, by considering their use in relation to academic skill development. It focuses on a set of workshops conducted within a graduate professional development course at Queen’s University (Canada) in early 2024. The first workshop examined commonalities in Western, English academic writing structures; identified how demystifying these structures supports academic writing and reading practices; and considered how GenAI tools that utilise large language models (LLMs) mimic these structures to enhance students’ awareness of GenAI’s potential applications and limitations, and to identify the processes inherent in academic work. In the second workshop, students critiqued discipline-specific examples of AI-generated academic assignments. By exploring the qualities of academic writing alongside GenAI outputs, the workshop series invited students to explore the possibilities of what might be achieved through human-AI collaboration and to articulate what can never be replicated by a tool without embodied knowledge. This paper presented this set of workshops as a possible model for discussing GenAI tools with students—a model that demonstrates how GenAI tools might be integrated into students’ academic practices in ways that are ethical and effortful and which support, rather than stifle, student creativity.